Transformasi Tradisi Among-Among pada Masyarakat Muslim Jawa di Desa Tanjung Medan: Perspektif Sosial Auguste Comte - Masriani Lubis (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
The among-among tradition is a religio-cultural practice of Javanese Muslim communities that functions as a medium of gratitude, prayer, and social solidarity. Amid the dynamics of modernization, this tradition has undergone shifts in its material aspects, implementation procedures, and patterns of social participation. The research problem addressed in this study is: how do the forms and driving factors of the transformation of the among-among tradition in the Javanese Muslim community of Tanjung Medan Village manifest, and how can these changes be analyzed through Auguste Comte’s theory of social change?. Unlike previous studies that primarily examine among-among as a cultural ritual or a symbol of social cohesion, this research specifically employs Auguste Comte’s theory of social evolution as an analytical framework to interpret its transformation within a contemporary rural Muslim context. Thus, the study not only describes the changes but also situates them within a classical sociological perspective. This study applies a qualitative descriptive approach. Data were collected through observation, in-depth interviews with six key informants, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing, with source triangulation to ensure validity. The findings indicate transformations in menu composition, food packaging materials, invitation distribution patterns, and a decline in children’s participation as the primary participants. These changes are influenced by internal factors (local innovations, social dynamics, and demographic shifts) as well as external factors (modernization, technological development, and cross-cultural interaction). From the perspective of Auguste Comte, these findings reflect a shift from a theological stage toward a more rational and functional pattern in social practice.  The results demonstrate that the transformation of the among-among tradition is not merely symbolic but also reflects a reorientation of values and rationality within the local Javanese Muslim community.